Sustainability, cost recovery and pricing for water in irrigation investment - Mergos G.J. (Aspects économiques de la gestion de l'eau dans le bassin méditerranéen, 1997)
Sustainable agricultural development is a desirable goal, but as a concept it cannot lead to practical project appraisal recommendations, unless it is properly defined and introduced in the project evaluation process as a set of selection rules. The critical link for ensuring sustainable development is to maintain ecological, operational and financial sustainability at the project level. Ecological sustainability is a well known concept, but financial sustainability needs some explanation. Financial sustainability is related to problems caused by the large recurrent cost burdens on government budgets and the need for frequent system rehabilitation of irrigation schemes. Since most countries face serious budgetary difficulties in financing their development plans, it is necessary to reconsider the basis on which irrigation projects operate and impose a principle of self-sustaining. Under such principle, the cost of operation and maintenance of irrigation projects (and perhaps the recovery of investment) should be internationalized. In addition, a mechanism should be introduced for assessing institutional performance and for encouraging farmers' participation and responsibility. Pricing and cost recovery issues should, as a principle, be part of project economic work. The well known rule 'price should equal short-run marginal cost' is far too simple to be practical and new types pricing policy are necessary. Equity and efficiency are generally the main issues. Hence, a presentation and discussion of alternative pricing rules as well as of price policy experience in irrigation investment becomes important. In addition, issues of water allocation methods and water rights are important for the establishment of an effective water management system. Finally, the relevance of water markets as a mechanism for the allocation of water is recently attracting considerable attention
Atelier sur les Aspects Economiques de la Gestion de l'Eau dans le Bassin Méditerranéen, 1995/05/17-19, Marrakech (Morocco)